2021
DOI: 10.1021/acsami.0c23164
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Decorated Silicon Nanowire Photocatalysts for Intracellular Production of Hydrogen Peroxide

Abstract: Hydrogen peroxide (H 2 O 2 ) plays diverse biological roles, and its effects in part depend on its spatiotemporal presence, in both intra-and extracellular contexts. A full understanding of the physiological effects of H 2 O 2 in both healthy and disease states is hampered by a lack of tools to controllably produce H 2 O 2 . Here, we address this issue by showing visible-light-induced production of exogenous H 2 O 2 by free-standing, gold-decorated silicon nanowires internalized in human umbilical vein endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…In just the past few years, a nascent field of faradaic delivery concepts for neuromodulation has begun to emerge. Recently, Tian and colleagues reported a photoactivated silicon/Au nanowire system for intracellular H 2 O 2 delivery, [ 34 ] suggesting this as a potent approach to enable novel experimental procedures to understand ROS effects. In pioneering works from Antognazza and coworkers, the photochemical production of peroxide/ROS by organic semiconductors, namely polythiophenes, was demonstrated at the level of several biological targets: charge‐transfer to redox proteins, [ 35 ] stimulation of transient‐receptor vanilloid subtype ion channels, [ 36 ] and ultimately control of stem cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In just the past few years, a nascent field of faradaic delivery concepts for neuromodulation has begun to emerge. Recently, Tian and colleagues reported a photoactivated silicon/Au nanowire system for intracellular H 2 O 2 delivery, [ 34 ] suggesting this as a potent approach to enable novel experimental procedures to understand ROS effects. In pioneering works from Antognazza and coworkers, the photochemical production of peroxide/ROS by organic semiconductors, namely polythiophenes, was demonstrated at the level of several biological targets: charge‐transfer to redox proteins, [ 35 ] stimulation of transient‐receptor vanilloid subtype ion channels, [ 36 ] and ultimately control of stem cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Application of new material systems, such as a low-dimensional carbon-based composite, 42 , 43 can potentially improve modulation efficiency. Advances in nanostructure synthesis and further modification on the nanoscale and atomic scale are promising to yield more robust signal transduction interfaces, where biomechanical sensing by the cellular machinery 44 or biocatalysis 45 may play additional roles. We believe that many paradigms previously successfully applied in energy science and catalysis can be adapted to improve bioelectronic devices.…”
Section: Discussionmentioning
confidence: 99%
“…Such a film could also bring benefits in biological applications that require H 2 O 2 . Phillips et al demonstrated that Au-sputtered Si NW films produced 6.2 μM/cm 2 H 2 O 2 in 30 minutes in water under visible light and without any sacrificial agents suitable for intracellular H 2 O 2 production[63]. However, the exact mechanism requires further studies, but it is believed the gold-silicon interface is responsible for the production of H 2 O 2 .…”
mentioning
confidence: 99%